2021
DOI: 10.3390/foods10071655
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Microbial Food Safety and Environmental Sustainability in the Fresh Produce Supply Chain

Abstract: Improving the environmental sustainability of the food supply chain will help to achieve the United Nations Sustainable Development Goals (SDGs). This environmental sustainability is related to different SDGs, but mainly to SDG 2 (Zero Hunger), SDG 12 (Responsible Production and Consumption), SDG 13 (Climate Action), and SDG 15 (Life on Land). The strategies and measures used to improve this aspect of the food supply chain must remain in balance with other sustainability aspects (economic and social). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 113 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…Numerous studies have consistently demonstrated that food safety risks predominantly occur within the food supply and processing chain [ 11 , 12 ]. Therefore, it is imperative to examine the issue of food safety from the perspective of the food supply chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have consistently demonstrated that food safety risks predominantly occur within the food supply and processing chain [ 11 , 12 ]. Therefore, it is imperative to examine the issue of food safety from the perspective of the food supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to examine the issue of food safety from the perspective of the food supply chain. Previous research has focused on exploring synergistic mechanisms within the supply chain to prevent food safety risks and the influence of government regulations [ 12 , 13 ]. For instance, Lupo et al [ 14 ] proposed that food supply chain risks can be mitigated through the implementation of mandatory preventive measures and the enforcement of penalties or sanctions, with joint responsibility shared among food operators and regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Although industrialization has made human life convenient, it has also given rise to environmental issues, such as global climate change, food shortage, and pollution. To overcome these problems, the United Nations proposed 17 Sustainable Development Goals (SDGs) for maintaining human health and establishing a sustainable society [18]. Natural resources or products form the basis of and are consumed during the economic activities 2 of 18 in developing and developed countries, causing industrial and environmental problems that need to be mitigated.…”
Section: Introductionmentioning
confidence: 99%
“…One of The Goals of Sustainable Development were set up in 2015 by the United Nations General Assembly is the fight against hunger, which includes ensuring food security [1,2]. An important problem threatening food safety is the formation of biofilms and the spread of pathogenic bacteria in the premises for the production and storage of food, as well as on equipment for its transportation [3,4].…”
Section: Introductionmentioning
confidence: 99%